Perception of freshmen students of the physiotherapy course about the profession: qualitative study (Research, Society and Development, 2022)
The present study identified the perceptions and motivations about the field of Physiotherapy of freshmen undergraduates. This is a descriptive qualitative study with 27 students who answered a structured questionnaire consisting of eight discursive questions about the concept, reasons and expectations related to Physiotherapy. The answers were transcribed in full, analyzed and categorized according to the Content Analysis method. Participants reported that the purpose of Physiotherapy is related to rehabilitation. This is a typical account of freshmen, possibly influenced by the stereotype related to Physiotherapy. However, the findings allow us to infer that the participants also have a perception about the broad role and attributions of the physiotherapist professional. Furthermore, among the factors that permeated the motivations for professional choice, it was observed that care, personal experiences, characteristics of physiotherapy and the course, frustration and the desire for personal fulfillment influenced this process.